Strategic Communications and Media for Climate-smart Agriculture Toolkit. Accelerating Impacts of CGIAR Climate Research for Africa - Trautman, Sabrina (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This toolkit covers topics such as: the impact of climate change on African agriculture and food systems; how we can transform African agriculture and food systems for a more sustainable and climate resilient future; the important national, regional, continental, and global initiatives to promote climate-smart agriculture, in Africa and worldwide; how to investigate and report key developments to target specific stakeholders, decision makers, networks towards desired behavior change; how to engage and report upcoming policy events (e.g., COP28); and how to engage with AICCRA partners on how media outputs and engagements can feed into national / regional programs.